Does ankle joint flexibility affect underwater kicking efficiency and three-dimensional kinematics? - Shimojo, H.; Nara, R.; Baba, Y.; Ichikawa, H.; Ikeda, Y.; Shimoyama, Y. (Journal of Sports Sciences, 2019)
Ankle flexibility is critical to obtain a high swimming velocity in undulatory underwater swimming (UUS). The present study investigated the Froude (propelling) efficiency and three-dimensional (3D) kinematics of human UUS following the extrinsic restriction of the ankle by tape application. In Experiment 1, swimmers (9 male and 8 female college swimmers) performed UUS trials involving normal swimming (Normal) and swimming with tape application at the ankle (Tape). Kicking frequency was controlled in both settings. UUS kinematics were obtained with a two-dimensional motion analysis. Swimming velocity significantly decreased during swimming with tape application compared with that during normal swimming (Normal, 1.33 m/s; Tape, 1.26 m/s, p < 0.05). The Froude efficiency was not affected (Normal, 0.77; Tape, 0.76), and ankle plantar angle did not decrease during swimming (Normal, 159.02°; Tape, 160.38°). In Experiment 2, lower limb rotations of a male swimmer were analysed using 3D motion analysis under the same conditions as Experiment 1. An insufficient forefoot rotation was observed during downstroke kicks (the phase of the highest acceleration to forward direction). These findings suggest that UUS velocity is affected by the mobility of end effector.